AN Empirical Study of Tourism Human Resources Management to Improving the Community Economy Around Jolotundo Umbul Bathroom, Klaten Regency - Prasetyo Ardi, Rudi (Media Wisata, 2024)
Human resources have an important role in the development of a country. Improving the quality of human resources as a development investment is very much needed, especially in developing countries such as Indonesia, where human resources are still lacking in terms of quality and productivity. To be able to overcome the problem of lack of quality and productivity of human resources in developing countries such as Indonesia. So it is necessary to understand ways to improve the quality of human resources through education, health, employment and migration. The quality of Human Resources (HR) is an absolute requitment for carrying out development. In this study, the authors used qualitative research methods to find out the sources of data related to the management of Human Resources at the Jolotundo Umbul Baths, namely through interviews with the managers of the Umbul Baths, the Tourism Office and the surrounding community. The condition of human resources at the Jolotundo Umbul Baths is considered to tbe lacking, aspecially in the tourism sector, so that tourism human resource management is needed to improve the economy of the community around the Jolotundo Umbul Baths